Assessment of Quality Parameters in Samples of Iraqi Honey - Dhia F. Al-Fekaiki; Wissam K. Al-Rubaie (University of Thi-Qar Journal of agricultural research, 2022)
This study was carried out on samples of honey that represented most of the governorates of Iraq from different plant sources. The estimation was made for the values ​​of indicators or criteria on which to determine the purity of honey, as the electrical conductivity values ​​ranged from 1205-322 µS/cm. The highest value was recorded in the H8 sample, while the lowest value was in the H1 sample, the proline content ranged within the limits of 181.7 - 398.3 mg/kg, as the H12 sample recorded the highest content of proline and the lowest content in the sample H8. as the highest value of diastase in sample H12 was 21 unit and the lowest value reached 8 units in samples H4 and H8, in While the highest activity of invertase was recorded in the H7 sample which amounted to 284.3 U/kg and the lowest activity in the H11 sample, which amounted to 107.5 U/kg. Also, the values ​​of HMF ranged between 7.6-40.3 mg/kg, as the maximum value of HMF was in northern eucalyptus honey (H2), while it was the lowest In northern floral honey (H5), the content of ascorbic acid was between 138.83-305.5 mg/kg, as it reached its maximum concentration in sample H15, while it was lower in sample H5.